Study of springs water quality as sources of potable water and for irrigation in Rezina district - Sandu, Maria; Mosanu, Elena; Gladchi, Viorica; Tarita, Anatol; Duca, Gheorghe; Spataru, Petru; Lupascu, Tudor; Sergentu, Efim; Lozan, Raisa; Jabin, Veaceslav; Turcan, Sergiu (Academia de Ştiinţe a Moldovei, 2010)
A spring is a component of the hydrosphere, where water ﬂows on to the surface of the earth from below the surface. Thus it is where the aquifer surface meets the ground surface. It may be the result of karsts topography where surface water has inﬁltrated the Earth’s surface, becoming part of the area groundwater. As sources of water supply in the Republic of Moldova underground waters constitute 15,2% (bore holes, springs and wells). The present work includes water quality investigations and aims to reveal local sources in river Nistru hydrographic basin (Rezina district) for drinking water provision in villages. Chemical composition of investigated spring’s water shows that in Rezina district 19% of springs are polluted with nitrogen compounds. Water of only 9% of springs is in conformity with the standard for drinking water. Water from 102 springs meets the requirements of irrigation that doesn’t present the risk of soil salinization (K > 18) – 1 383 L/min.
Keywords: water quality